Design a monitoring system for the output voltage, current, and frequency of a 3-phase generator in a mini power plant module at the instrumentation engineering department - Raafi'u, Brian; Iskandarianto, Fitri Adi; Darwito, Purwadi Ags; Fadilah, Titin Nur; Badrul Alam, Rakmad Amrinsyah; Adhim, Fauzi Imaduddin; Ash-Shiddieqy, Rizaldy Hakim (Faculty of Vocational Studies - Research Center, DRPM ITS, 2024)
Electrical energy is a requirement in everyday human life. The stability of the electrical energy generation system is something that must be considered, one of the power generation instruments that are often used is a generator, which converts mechanical energy into electrical energy. The generator has physical variables that must be maintained, including voltage, current and frequency. So as to know the amount of voltage and current produced by the generator, a system is made that can measure the amount of current, voltage and frequency produced by the generator with a portable system (plug and play). In this system, the generator output parameters are monitored using various sensors including the ZMPT101B voltage sensor to measure the generator output voltage, the ACS712 sensor to measure the current variable and the zero crossing detector to measure the frequency variable. From the test data of the monitoring system, the results obtained are the ZMPT101B voltage sensor which has an error reading of 0.01 for the ACS712 sensor reading error of 0.09 and for the frequency sensor reading error of 0.01. These three sensors were successfully used in the monitoring system of voltage, current and generator output frequency in the mini power plant module.